Erratum to: Combined analysis of Belle and Belle II data to determine the CKM angle ϕ3 using B+ → D(K0Sh+h−)h+ decays - Patra, Sourav (Springer Nature, 2022)
Page 20, footnote: Of the methods available in GammaCombo, we used the profile likelihood method, also known as the PROB method. With the PLUGIN method, which uses pseudo-experiments and the best fit values of the nuisance parameters, the central values of our results do not change, and the change in the uncertainty is of the order of the total experimental systematic uncertainty.
Only IISER Mohali authors are available in the record.
Keywords: Erratum to; Belle and Belle; II data to determine; CKM angle ϕ3 using B+